Nearly Quadratic Mappings over p-Adic Fields - M. Eshaghi Gordji; H. Khodaei; Gwang Hui Kim (Abstract and Applied Analysis)
We establish some stability results over p-adic fields for the generalized quadratic functional equation ∑k=2n∑i1=2k∑i2=i1+1k+1⋯∑in-k+1=in-k+1nf(∑i=1,i≠i1,…,in-k+1nxi-∑r=1n-k+1xir)+f(∑i=1nxi)=2n-1∑i=1nf(xi), where n∈N and n≥2.